2010
DOI: 10.1002/cphc.200900857
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐ice on Boron Nitride Nanomesh: Accessing Proton Disorder

Abstract: Water was investigated on a h-BN/Rh(111) nanomesh template using variable temperature scanning tunneling microscopy (STM) and density functional theory (DFT) calculations. Below 52 K, two distinct phases self-assemble within the 3.2 nm unit cell of the nanomesh that consists of "holes" and "wires". In the 2 nm holes, an ordered phase of nano-ice crystals with about 40 molecules is found. The ice crystals arrange in a bilayer honeycomb lattice, where hydrogen atoms of the lower layer point to the substrate. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
57
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 24 publications
7
57
1
Order By: Relevance
“…In ref. [6], we already showed that 42 water molecules extracted from the M4 model, without any relaxation, generate a local modulation of the electrostatic potential which closely resembles the experimental observation. Here, 38 M4 water molecules are optimized in the pore of the nanomesh, and the simulated STM image are in agreement with the experiment, where spots of different brightness identify molecules at different height.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In ref. [6], we already showed that 42 water molecules extracted from the M4 model, without any relaxation, generate a local modulation of the electrostatic potential which closely resembles the experimental observation. Here, 38 M4 water molecules are optimized in the pore of the nanomesh, and the simulated STM image are in agreement with the experiment, where spots of different brightness identify molecules at different height.…”
Section: Discussionsupporting
confidence: 79%
“…By standard structure optimization, the overlayer corrugates and forms the characteristic pore and wire regions, where the pore is a hexagonal- The actual number of water molecules in the pore might also affect the final structure. From the experimental data we know that there should be (20±5) per layer [6], therefore 38 molecules is in the right range. It is even possible that molecules move fast from the cluster to the wire and in the opposite direction, thus changing the conditions at the rim.…”
Section: B Water Cluster On the Nanomeshmentioning
confidence: 97%
“…Results on the h-BN/Cu(111) systems have been reported within an extended study on several TMs [21]. More theoretical work on these systems is available in the context of additional molecular interactions (water on h-BN/Rh(111) [64,65], metal atoms on h-BN/Rh(111) [27,66], hydrogen adsorption and intercalation [18,67]), and in direct connection with experiments [2,5,10,19,23,68].…”
Section: H-bn/metal Interfacementioning
confidence: 95%
“…Such inhomogeneity can lead to the formation of distinct nanometre-scale water structures, as observed on a boron nitride nanomesh 18 , or can disrupt the formation of an ordered phase, as observed on stepped Pt surfaces 19 . On oxide surfaces, an inhomogeneous distribution of defects or the presence of different facets can lead to a strongly varying distribution of OH groups, creating large variations in hydrophilicity over short length scales 16 .…”
mentioning
confidence: 99%